1995
DOI: 10.1161/01.cir.91.5.1341
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Variation in the Efficacy of Tissue-Type Plasminogen Activator

Abstract: There is a circadian variation in the ability of TPA to rapidly open coronary arteries, with highest efficacy between noon and midnight. This complements clinical and in vitro knowledge of increased morning thrombosis and is concordant with knowledge of increased morning thrombosis and is concordant with knowledge of a fibrinolytic profile that is more favorable for evening lysis. This finding has implications for understanding the circadian pathophysiology of myocardial infarction and for its chronotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
1
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(60 citation statements)
references
References 22 publications
3
53
1
2
Order By: Relevance
“…22) Enhanced secretion of PAI-1 may contribute to both the increased incidence of acute atherothrombotic events and the decreased efficacy of thrombolytic therapy. 23) The levels of adiponectin exhibit a diurnal rhythm with a significant decline at night in healthy men. 24) Conversely, serum levels of adiponectin are diminished in humans and animals with insulin resistance and obesity.…”
Section: Introductionmentioning
confidence: 99%
“…22) Enhanced secretion of PAI-1 may contribute to both the increased incidence of acute atherothrombotic events and the decreased efficacy of thrombolytic therapy. 23) The levels of adiponectin exhibit a diurnal rhythm with a significant decline at night in healthy men. 24) Conversely, serum levels of adiponectin are diminished in humans and animals with insulin resistance and obesity.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, t-PA seems to be more effective particularly during diurnal hours, whereas a higher resistance to thrombolysis in the early morning, associated with plasminogen activator inhibitor-1 level increase, has been reported. 12,[35][36][37] This has also been suggested by a significant difference in the proportion of diurnal and nocturnal early recanalization 2 hours after t-PA bolus. 24 In the SITS cohort, data on early recanalization are not available, whereas we found the same proportion of reversal of the HMCAS, a surrogate marker of recanalization, 38 22 to 36 hours after diurnal or nocturnal treatment.…”
Section: Discussionmentioning
confidence: 77%
“…[1][2][3][4][5][6] An increased incidence of stroke has been reported during the weekend and on Monday, 3,7,8 whereas other studies reported Wednesday as the most risky day; and others did not find significant variations among the days of the week. [9][10][11] Circadian changes of biological hemodynamic and hemostatic processes, including a reduction of fibrinolytic activity with increased thrombogenic condition in the late-morning hours 12 and on weekends, 13 have been advocated to explain temporal variations of stroke onset.…”
mentioning
confidence: 99%
“…136 Indeed, a high level of tissue plasminogen activator inhibitor 1, associated with low fibrinolytic activity, was found to be an independent risk factor for first acute MI in both men and women. 137 The combination of increased platelet aggregability, 138 blood viscosity, 139 and thrombotic activity, 19 as well as decreased fibrinolytic activity, 135,[140][141][142] would not only increase the size of an otherwise nonoccluding thrombus but would also increase its resistance to thrombolysis. …”
Section: Other Hematologic Factorsmentioning
confidence: 99%